Maternal Environmental Temperature During Gestation Affects Renal Function Indices and Oxidative Stress in The Kidney of Offsprings of Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
Maternal exposure to increase temperature reduces birth weight. Low birth weight is related to adult-onset of non-communicable diseases. In this study, the effects of maternal exposure to various environmental temperatures during gestation on renal function and oxidative stress indices in offspring of Wistar rats were assessed. Fifteen pregnant Wistar rats were divided into 3 groups (n=5). The animals were housed in specialized thermoregulatory cages at 250C, 320C and 390C respectively. The animals were allowed to deliver spontaneously. At 12 weeks of age, the offspring were euthanized. Urea concentrations in seru, urine and creatinine clearance were assessed as renal function indices. Renal superoxide dismutase (SOD), catalase and malondialdehyde (MDA) activities were estimated as indices of oxidative stress. Histopathology and histomorphometry of the kidney were also assessed. Concentrations of urine creatinine and creatinine clearance of temperatureup 39°C were significantly higher than that of the 250C and 320C groups in both male and female offspring. Catalase and SOD activities in kidneys of the male offspring were significantly decreased in temperature group 320C when compared to temperature groups 250C and 390C. Meanwhile, MDA level was significantly higher in the320C group.In the female offspring, exposure to 250C significantly increased the concentration of serum creatinine, urea and renal MDA levels compared to other temperature groups. However, SOD activities were lowered in the 250C group. In conclusion, maternal environmental temperature during gestation affects renal function and oxidative stress indices in offspring of Wistar rats. These effects may be affected by sex of the offspring.